Assessment of Changes in Channel Width and Braiding: The Implications on Flooding Upstream of Shiroro Reservoir in river Kaduna, Kaduna State, Nigeria - O. G. Salawu; D. Leke (Journal of Applied Sciences and Environmental Management, 2024)
The objective of this paper was to presents potential implications of flooding on changes in channel width and braiding patterns within the nine study reaches upstream of the Shiroro Reservoir of River Kaduna, Kaduna Nigeria using standard methods for data acquisition and analysis. Preliminary findings reveal substantial alterations in channel morphology, characterized by an increase in channel width and a shift towards braided patterns in some of the study segments of River Kaduna. These changes are attributed to factors such as deforestation, urbanization, and land use changes within the river's catchment area resulting sediment released into the river. The hydrological consequences of these alterations, including increased flood risk in the upstream regions, sediment transport dynamics, and their implications for the functionality of the Shiroro Reservoir as a flood control mechanism has been pointed out. The outcomes of this study not only contribute to a better understanding of the evolving hydro- geomorphological dynamics of the Kaduna River but also provide valuable insights for sustainable river management practices and flood risk mitigation in the region. As Nigeria grapples with increasing challenges related to climate change and population growth, the findings presented in this paper hold significant relevance for policymakers, water resource managers, and communities living in flood-prone areas along River Kaduna.